Utilization and reproducibility of World Endoscopy Organization post-colonoscopy colorectal cancer algorithms: retrospective analysis - Beaton, David; Beintaris, Iosif; Rutter, Matthew D. (Endoscopy, 2021)
Background Colorectal cancer (CRC) diagnosed following a cancer-negative colonoscopy is termed post-colonoscopy CRC (PCCRC). In addition to calculating PCCRC rates, the World Endoscopy Organization (WEO) recommends review of individual PCCRC cases, including categorization into interval/non-interval PCCRCs, and root cause analysis to determine the most plausible explanation. We aimed to test the usability, reproducibility, and outcomes of the WEO algorithms.Methods All CRC cases diagnosed from January 2015 to December 2016 in a single organization were cross referenced with local endoscopy and pathology databases to identify cases of PCCRC. We assessed: 1) WEO most plausible explanation for PCCRC; and 2) WEO PCCRC interval/non-interval subtype categorization. Interobserver agreement was measured using Cohen’s kappa (κ). Cases with interobserver variation underwent panel discussion to reach consensus.Results Among 527 patients with CRC, 48 PCCRCs were identified. A consistent most plausible explanation was found in 97 % of cases, showing almost perfect agreement (κ = 0.94). Most PCCRCs (66 %) were attributed to “possible missed lesion, prior examination adequate.” Interval/non-interval categorization was consistent in 77 %, showing substantial agreement (κ = 0.67). Following panel discussion, consensus was reached in all cases. Overall, 15 % were categorized as interval and 85 % as non-interval PCCRCs (12 % type A, 31 % type B, and 42 % type C).Conclusions Review of PCCRC cases using WEO recommendations was performed accurately at a local level using readily available clinical information. The high number of non-interval type B PCCRCs suggests a significant proportion of PCCRCs could be avoided by better adherence to recommended surveillance intervals.